Guide d'observation des champignons lignivores rencontrés sur les arbres d'ornement (Grand Lyon)
ARMILLARIA MELLEA(L’AEU^ìLAIRE COULEUR DE MIEL) CORIOLUS VERSICOLORE (LE CORIOLE CHATOYANT) FISTUL1NA HEPATICA (LA FISTUL1NE HEPATIQUE) FOMES FOMENTARIUS (L’AMADOUVIER) GANODERMA APPLANATUM (LE CANODERME APLANI) GANODERMA LUCIDUM (LE GANODERME LUISANT) HAPLOPORUS CYTISINUS (L’HAPLOPORE DU FRENE) INONOTUS IHSPIDUS (LE POLYPORE HERISSE) LAETIPORUS SULFUREUS (LE POLYPORE SOUFRE) MERIPULUS GIGANTEUS (LE POLYPORE GEANT) PHAEOLUS SCWEINITIZTI (LE POLYPORE DE SCHWEINITZ) PHELLINUS PINI (LE PHELLIN DU PIN) PHELLINUS POMACEUS (LE PHELLIN DES ARBRES FRUITIERS) PHELLINUS PUNCTATUS (LE PHELLIN TACHETE) SCHIZOPHYLLUM COMMUNE (LE SCHIZOPHYLE COMM UN) USTULINA DEUSTA (ASCOMYCETE )